Diseño de planta para la clasificación y transformación de residuos sólidos aprovechables en la comuna 6 del municipio de Neiva - Huila. (2023)
In the capital of the Huila department, in Neiva, different environmental problems can be evident in relation to the inadequate management and treatment of solid waste, especially usable inorganic solid waste. This is due to the companies that provide station, classification and utilization services. Where these companies have irregularities is the infrastructure and it does not allow them to be aligned with regulations.